Forests regenerate on titled Indigenous territories: A multiscale interdisciplinary analysis of 25 Indigenous communities over 40 years in the Peruvian Amazon - Bennett, A.C.; Larson, A.M.; Zamorra Ríos, A.; Gamarra Agama, S.; Monterroso, I. (Center for International Forestry Research, 2021)
Tropical forests are highly regenerative, and people who live there often support natural regeneration and reforestation, so it is critical to report on these and not only on forest loss (deforestation). Titling Indigenous community territories (ICTs) can prevent outsiders from taking over degraded forest areas for other uses, thereby supporting more forest regeneration.